JUSTICE (AL MASHLAHAH) FOR THE ECONOMIC DIMENSION - Andi Fariana; Sufiarina Sufiarina (Universitas Islam Negeri Mataram, 2019)
The sharia (Islamic) activity has seen a rapid development, not onlyin its impact on growth in the international community, but also in the historyand development of Islamic Law, which is part of The Living Law. Therefore,prompt actions are needed to oversee the growth using the concept, theory,laws and regulations, which are part of the Islamic Economic Law and beingpart of the National Legal System. One of the legal system principles is theconcept of justice that constitutes the supreme goal of the Law, and the Quranpromotes fairness and forbids partiality in any transactions.This paper emphasizes the importance of justice which is the goal of law andin the qur’an, justice matters are mentioned in various dimensions. Meanwhile,the concept of justice in the economy is defined as social justice or al mashlahah.Defining Al Mashlahah as social justice in economic dimensions justifies thatGod’s purposes to reveal various rules including rules implementing economicactivities is to achieve justice for all parties. Islam puts Mashlahah as the centralidea of maqashid ash shari’a as the justice philosophy in the Islamic perspectiveis a universal and comprehensive justice. If the ultimate goal in establishingvarious economic policies is to maintain consciousness of justice then thedecision makers should always institute justice for all as the basic policy inimplementing al maslahah in economic activities especially in Indonesia.